A Variable Frequency Drive Trainer for use in a University Agricultural Electricity Course - Teekell, Colton R.; Hilaire, Patterson P.; Johnson, Donald M. (Journal of Agricultural Systems, Technology, and Management, 2019)
This article describes the construction and evaluation of a relatively inexpensive (< 600.00) variable frequency drive (VFD) trainer for use in an undergraduate agricultural electricity course. The trainer met the design criteria of safety, cost, availability of both keypad and remote operation, and programmability through the keypad. We developed a student laboratory activity for use with the trainer and students (n = 21) in an undergraduate agricultural electricity course used the activity and trainer in spring 2018. We assessed students’ prior familiarity and experience with VFDs and their perceptions of the effectiveness of the trainer and activity as a way to learn about VFDs. Prior to classroom instruction and the laboratory activity, students indicated they had little if any exposure to VFDs. After completion of the laboratory activity, 100% of students agreed the activity was effective in helping them learn to program and operate a VFD. Based on the trainer’s effectiveness in this pilot test, we intend to construct additional trainers for use in the undergraduate agricultural electricity course.